Mr. Magoo. The theatrical cartoons 1949-1959 [videorecording (DVD)] - Backus, Jim; Conried, Hans; Crosby, Kathryn, 1933-; Bernardi, Herschel; Hickman, Dwayne (Classic Media, LLC, 2014)
Voiced by Jim Backus, Mr. Magoo is a wealthy, short-statured retiree who gets into a series of sticky situations as a result of his nearsightedness, compounded by his stubborn refusal to admit the problem. However, through uncanny streaks of luck, the situation always seems to work itself out for him, leaving him no worse than before.